Chemical composition and larvicidal activity of essential oils from Peganum harmala, Nepeta cataria and Phellodendron amurense against Aedes aegypti (Diptera: Culicidae) - Shengxiang Yang; Mingsheng Bai; Jian Yang; Yuan Yuan; Yamei Zhang; Jianchun Qin; Yi Kuang; Diego A. Sampietro (Elsevier, 2020)
Essential oils from aerial parts of the herbs Peganum harmala and Nepeta cataria, and leaves of the tree Phellodendron amurense were analyzed by GC-FID and GC-MS, and their larvicidal activities were assayed on the early fourth instar larvae of Aedes aegypti. The major constituents of the oils were limonene (14.5%) and thymol (11.5%) in P. harmala, thymol (46.5%), 4aα,7α,7aβ-nepetalactone (18.3%) and 4aα,7β,7aα-neptalactone (19.7%) in N. cataria, eugenol (14.5%) andγ-eudesmol (9.5%) in P. amurense.The oil of N. cataria had a strong larvicidal activity (LC50 < 50 µg/mL; LC90 < 86.8 µg/mL) on A. aegypti while the remaining oils showed a moderated killing effect. The larvicidal activity of N. cataria oil was associated to the contents of 1,8-cineol, camphor, 4aα,7α,7aβ-Nepetalactone, 4aα,7β,7aα-Nepetalactone and thymol. Our results indicate that the oil of N. catariadeserves to be used as a source of larvicidal agents against A. aegypti.